Population Structure and Anthropogenic Pressure of Sea Urchin Utilisation (Diadema setosum) on Shallow Coral Reefs of Dedap Island, Batam - Pitrin Octca Manihuruk; Yarsi Efendi; Fauziah Syamsi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Diadema setosum is a key species in maintaining coral reef stability through its role in controlling algal growth. However, exploitation for consumption and trade of its gonads by coastal communities has generated anthropogenic pressures that threaten population sustainability. This study aims to assess the population structure and utilisation pressure on   D. setosum in the shallow coral ecosystem of Dedap Island, Batam City. Methodology: Observations were carried out at five stations using a 50-metre belt transect method with 5×5 m quadrat plots. Data were analysed through descriptive statistics to determine density and distribution, while correlation and regression analyses were applied to examine the influence of environmental parameters (temperature, dissolved oxygen, salinity, and pH). Structured quantitative interviews with local fishermen were conducted to obtain information on harvesting practices. Results: The population density ranged from 0.180 to 0.292 ind/m², with a clustered distribution pattern observed at stations farther from human activity. Regression results indicated that temperature significantly increased density, while dissolved oxygen and pH had significant negative effects. Fishermen reported daily harvesting during low tide with yields of 2–3 kg of gonads per person. These findings demonstrate exploitation pressure on D. setosum, underscoring the need for ecosystem-based management. Contribution: The novelty of this study lies in integrating ecological surveys with socio-economic data, offering comprehensive insights for locally adapted conservation strategies.